Understanding Common Rationales Adopted in Healthcare Price Setting Across the Private Healthcare Sector in Sri Lanka: A qualitative study - Kanchana Sajeeva Narangoda; Joon Soo Park; Marc Tennant; Estie Kruger (ACHSM, 2022)
Background / Objectives: The Sri Lankan healthcare system consists of public and private sectors. In terms of capacity, the public sector dominates the provision of care across curative, preventive and outpatient care. The private sector, too, has grown rapidly in recent years but was mainly confined to providing curative, diagnostic and outpatient care. Since, there are little or no studies conducted in Sri Lanka thus far, the objective of this study was to understand the current approaches adopted in determining the base of healthcare payments. This study also investigated the economic and administrative processes involved in determining the level of healthcare pricing in the private sector healthcare industry in Sri Lanka. Method: This qualitative study investigated the rationales adopted in healthcare pricing by healthcare administrators in the private sector. Structured interviews were conducted and thematic analysis were applied to interview data collected and analysis. Results: Five key themes, which influenced pricing, were identified from the interviews. These themes included influence from medical practitioners/clinicians, competitor pricing, price adjustment/profit margins, consumables and staff, and economic demands. There was a consensus that competitor pricing and seniority of the practicing clinicians had an impact on pricing.  Conclusion: This study revealed that the base of payment in private sector healthcare is fee for service (FFS). Adopting popular international approaches such as Diagnostic Related Groups (DRGS) was not shown in this study. Further, it was evident that the Sri Lankan private healthcare sector administrators unilaterally fix pricing based on the identified key themes without adequately consulting the healthcare payers and users.